Soil amenndments - Sholukha, Т. А. (ТДАТУ, 2021)
Organic amendments are more sustainable and environmentally friendly, but have low nutrient levels. Inorganic amendments are easy to use, work immediately, but are expensive and the amount of use is limited.
Keywords: composted manure; soil